The war in Croatia, 1991-1995 - Bjelajac, Mile (Array, 2009)
Chapter describes and analyses the development of the crisis in Croatia and the ensuing war (1991-1995). Main purpose of the chapter was to establish basic and indisputable facts and reexamine historical controversies as a basis for further research.